God Image as a Function of Self-Esteem and Locus of Control - Benson, Peter L. (Journal for the scientific study of religion, 1973)
A cognitive consistency framework was adopted to predict that a believer's level of self-esteem and his location on the locus of control dimension influence his description and definition of God. On a sample of 128 Catholic subjects with approximately identical religious backgrounds, self-esteem was positively related to loving-accepting God-images and negatively to rejecting images. Locus of control was unrelated to controlling beliefs. Statistical and methodological controls were utilized to offer an interpretation that self-esteem may be a major determinant of God-images. It was proposed that these findings have important implications for understanding the dynamics of personal religion.